The Problem of Substance - Batiščevas, Henrikas (Problemos, 1970)
The standpoint of dialectics of substance and of cultural-historic subject is the standpoint of the developed and developing personality which is no longer ascribing the world anything to place the weight of responsibility on – some substantial Absolute and Guarantor. This dialectics conveys simultaneously (a) subjectivism that makes the very (falsely understood) subject closed, sufficient in himself, needing no substantial prerequisites; (b) objectivism which makes Nature, with man in it as its part, substantially closed (disallowing of new in principle possibilities).